Anaesthetists' experiences and practices of perioperative peripheral nerve blocks for adult limb surgery - Scharf, Liesel Anne (My University, 2019)
The benefits of regional anaesthesia in the perioperative period are well recognised, but exposure and training may be inadequate or inconsistent, and procedural aspects can show variation and inconsistencies. This study describes the experiences and practices of perioperative peripheral nerve blocks for adult limb surgery in the Department of Anaesthesiology at the University of the Witwatersrand. Data were obtained from a researcher-developed questionnaire completed anonymously by consenting anaesthetists at departmental academic meetings from March to June 2017. This study identified areas where knowledge and current practice may be improved on this academic circuit. These areas include the minimum monitoring used when performing blocks, aseptic precautions when performing blocks, and preparing for and being confident in the management of severe local anaesthetic systemic toxicity. The barriers to performing peripheral nerve blocks were identified. The need for additional and improved training in regional anaesthesia was recognised
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesiology Johannesburg, 2019